Building Financial and Health Literacy at Older Ages: The Role of Online Information. Issue 3 (19th March 2019) - Bavafa, Hessam; Liu, Junhao; Mukherjee, Anita
Abstract : Improving financial and health literacy is an important step in reducing economic vulnerability in older age, yet the means by which individuals accumulate these types of human capital remains an open question. This article evaluates the impact of online search activities on the levels of financial and health literacy. We find that using the internet for such information increases literacy significantly: doing so frequently (versus not at all) increases financial literacy by 16%, and health literacy by 12%. Our results are robust to alternative measures of financial literacy. They are also robust to an instrumental variable approach using other web skills such as email use to proxy for how individuals use the internet.